Early virological failure and HIV drug resistance in Ugandan adults co-infected with tuberculosis. Issue 1 (December 2017) - Braun, Amrei; Sekaggya-Wiltshire, Christine; Scherrer, Alexandra; Magambo, Brian; Kambugu, Andrew; Fehr, Jan; Castelnuovo, Barbara
Abstract Purpose This cross-sectional study took place in the integrated tuberculosis (TB) clinic of a large outpatient clinic for HIV-infected patients in Kampala, Uganda. The purpose of this study was to describe the proportion of TB/HIV co-infected adults with virological failure, type and frequency of HIV drug resistance-associated mutations, and the proportion of patients with suboptimal efavirenz levels. Methods HIV-1 plasma viral loads, CD4 cell count measurements, and efavirenz serum concentrations were done in TB/HIV co-infected adults. Genotypic resistance testing was performed in case of confirmed virological failure. Results After a median time on ART of 6 months, virological failure was found in 22/152 patients (14.5%). Of 147 participants with available efavirenz serum concentration, 26 (17.6%) had at least one value below the reference range, including 20/21 (95.2%) patients with confirmed virological failure. Genotypic resistance testing was available for 16/22 (72.7%) patients, of which 15 (93.8%) had at least one major mutation, most commonly M184V (81.2%) and K103NS (68.8%). Conclusion We found a high proportion of TB/HIV co-infected patients with virological failure, the majority of which had developed relevant resistance-mutations after a median time on anti-retroviral treatment (ART) of 6 months. Virological monitoring should be prioritized in TB/HIV co-infected patients in resource-limited settings.